Peramalan Nilai Tukar Petani Subsektor Tanaman Pangan di Nusa Tenggara Timur Menggunakan Metode SARIMA - Muzaki, Fais; Agustina, Neli (Seminar Nasional Official Statistics, 2024)
The economy in East Nusa Tenggara (NTT) is dominated by the agricultural sector with the largest contribution to the NTT PDRB in 2023. In the same year NTT became the province with the lowest farmer’s terms of trade (NTP) and becoming a benchmark of farmer welfare in NTT is not good enough. Therefore, this study aims to analyze the general picture of NTPP in NTT in the January 2016 – June 2024 data period and predict some future period with SARIMA method. Forecasts with the ARIMA model (0,1,0)(0,1,1)12 produced a MAPE of 2,3553%. The results of the forecasts for the next year for the period July 2024 – June 2025, indicate that the NTPP figure is below 100, meaning that food crops farmers in the NTT are not well enough. The outcome of this forecast is expected to be considered by the government in an effort to improve the well-being of food crops farmers.